Identification of antipsychotic side effects in Schizophrenia patients using Naranjo algorithm at Jambi Psychiatric Hospital - Yuliawati; Istarini, Attiya; Kamariyah; Yuliana; Lestari, Uce; Sofyan, Indah Sri Wulan; Apriyanti, Sofia Elisa (Proceedings Academic Universitas Jambi, 2025)
Background: Schizophrenia is a chronic mental disorder that requires long-term antipsychotic therapy. However, the use of antipsychotics may lead to adverse drug reactions (ADRs) that can affect patients’ quality of life. Objective: This study aimed to identify the types and likelihood of antipsychotic-related side effects among patients with schizophrenia using the Naranjo Algorithm. Methods: A descriptive observational study was conducted in September 2025. Data were collected through structured patient interviews and verified using medical records. The probability of ADRs was assessed using the Naranjo Algorithm, and the data were analyzed descriptively. Results: Among 119 patients with schizophrenia, 12 met the inclusion criteria. These 12 patients experienced a total of 23 ADR events. Based on the Naranjo Algorithm, 4 patients (33.33%) were categorized as probable and 8 (66.67%) as possible. The most common adverse effects were severe sedation (6 cases, 29.09%) and weakness (6 cases, 29.09%), followed by acute dystonia, mouth stiffness, and hypotension (each 8.70%). Less frequent events included hyperglycemia, hypertension, leukocytosis, slurred speech, and hypersalivation (each 4.35%). Conclusion: Most adverse effects showed a possible to probable causal relationship with antipsychotic use. The Naranjo Algorithm proved useful for identifying ADRs and supporting pharmacovigilance activities in psychiatric settings. Enhanced clinical monitoring and patient education are recommended to minimize serious adverse effects.